Pierson syndrome presenting as Alport syndrome: A case report - Santa, Samina Masud; Diba, Tahmina Akter; Mamun, Abdullah Al; Begum, Afroza; Haque, Syed Saimul (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Pierson syndrome is an autosomal recessive disorder, characterised by congenital nephrotic syndrome and progressive renal failure. Patient of this syndrome may have some ocular abnormalities. We report a 46 month old girl with Pierson syndrome whose renal biopsy showed features suggestive of Alport syndrome. Genetic study report showed laminin b2 (LAMB2) mutation which presents as nephrotic syndrome, type 5 with or without ocular abnormalities and Pierson syndrome, and tripartite motif containing8 (TRIM8) mutation which presents with focal segmental glomerulosclerosis and neurodevelopmental syndrome. The patient was given supportive therapy. Bangabandhu Sheikh Mujib Medical University Journal 2023;16(3): 178-181